Prevalence of hypertension and its associated risk factors among Kolkata-based policemen: a sociophysiological study - Anurupa Sen,; Moumita Das,; Subhashree Basu,; Gouriprosad Datta, (Universiti Kebangsaan Malaysia, 2015)
Background: In India, very sparse data are available on the prevalence of noncommunicable diseases such as hypertension among the police force, as a specific occupational group. Objectives: To determine the prevalence of hypertension and its associated risk factors among the policemen of a metropolitan city, Kolkata, West Bengal, India. Materials and Methods: A total of 916 men (policemen = 507, civilian = 409) were randomly selected from different regions of central Kolkata, and the age ranged from 20 to 60 years. Blood pressure, anthropometric parameters, lifestyle pattern, and family history of hypertension were recorded. All statistical computations were performed with SPSS, version 20.0. Results: The prevalence of hypertension [systolic blood pressure (SBP) X 140 mm Hg, diastolic blood pressure X 90 mm Hg, or use of antihypertensive drugs] was observed among 32.5% of policemen, which was significantly higher when compared with the civilians (P o 0.01). Behavioral habits and obesity indices were also higher among the policemen (P o 0.05). Regression analysis identified age, body mass index (BMI), SBP, history of parental hypertension, and consumption of smokeless tobacco as the risk factors of hypertension. As obtained from receiver-operating characteristics analysis, the suggested cutoff values for BMI were 23.64 (kg/m2), for age 47.53 year, and for SBP 135 mm Hg. Conclusion: The findings revealed that notable numbers of Kolkata-based policemen are hypertensive than civilians and lifestyle modification along with healthcare strategies must be planned for this special population.